Retirement and Consumption in a Life Cycle Model - Blau, David M. (Journal of Labor Economics, 2008)
Consumption expenditure declines sharply at the time of retirement for many households, but the majority maintain a smooth consumption path. A simple life cycle model with uncertainty about the time of retirement can account for this pattern. A richer version of the model is calibrated to data from the Health and Retirement Study (HRS). The median change in consumption expenditure at retirement generated by the model is zero, while the mean is negative, matching the HRS data. However, the magnitude of the drop in consumption among households that experience a decline is too small in the model compared to the data.